Glucose uptake heterogeneity of the leg muscles is similar between patients with multiple sclerosis and healthy controls during walking. Issue 2 (February 2015) - Kindred, John H.; Ketelhut, Nathaniel B.; Rudroff, Thorsten
Abstract Background Difficulties in ambulation are one of the main problems reported by patients with multiple sclerosis. A previous study by our research group showed increased recruitment of muscle groups during walking, but the influence of skeletal muscle properties, such as muscle fiber activity, has not been fully elucidated. The purpose of this investigation was to use the novel method of calculating glucose uptake heterogeneity in the leg muscles of patients with multiple sclerosis and compare these results to healthy controls. Methods Eight patients with multiple sclerosis (4 men) and 8 healthy controls (4 men) performed 15 min of treadmill walking at a comfortable self-selected speed following muscle strength tests. Participants were injected with ≈ 8 mCi of [18F]-fluorodeoxyglucose during walking after which positron emission tomography/computed tomography imaging was performed. Findings No differences in muscle strength were detected between multiple sclerosis and control groups (P > 0.27). Within the multiple sclerosis, group differences in muscle volume existed between the stronger and weaker legs in the vastus lateralis, semitendinosus, and semimembranosus (P < 0.03). Glucose uptake heterogeneity between the groups was not different for any muscle group or individual muscle of the legs (P > 0.16, P ≥ 0.05). Interpretations Patients with multiple sclerosis and healthy controls showed similar muscle fiber activity during walking. Interpretations of these results, with respect to our previous study, suggest that walking difficulties in patients with multiple sclerosis may be more associated with altered central nervous system motor patterns rather than alterations in skeletal muscle properties.